The Effect of Perchloroethylene (PCE) Exposure Toward Frequency of Micronucleus Formation in Buccal Mucosal Ephitelia of Dry Cleaning Employees - Julianti, Rosmayda Ria; Brahmadhi, Ageng; Romdhoni, Muhammad Fadhol; Riyanto, Refni (Journal of Medicine, 2019)
Background: Perchloroethylene is one of the main ingredients used in the dry cleaning industry. Continuous inhalation of Perchloroethylene particles can cause genetic damage that can be marked by the appearance of micronucleus. Micronucleus formation of excessive buccal mucosal is one of the early signs of malignancy in the oral cavity. Objective: To determine the effect of Perchloroethylene exposure toward frequency of micronucleus formation in buccal mucosal epithelial of dry cleaning employees in Banyumas Regency. Materials & methods: This study uses cross-sectional design with primary data that is the preparation of buccal mucosal smear from 22 dry cleaning employees as exposed group and 22 subjects are not exposed to Perchloroethylene as control group. The buccal epithelial cells are collected using a spatula and then smeared on an object glass and colored using Giemsa. Micronuclear frequencies are calculated per 1000 cells using a light microscope. Results: The difference of micronucleus frequency between two groups (p = 0.000) is obtained. The duration of work has correlation with medium correlation strength to the forming frequency of micronucleus formation, whereas age has strong correlation to the forming frequency of micronucleus formation. The correlation between age and work duration with the forming frequency of micronucleus formation is significant (p = 0.000 and p = 0.07) Conclusions: There is influence of Perchloroethylene exposure toward frequency of micronucleus formation. The duration of work and age are significantly correlated with the forming frequency of micronucleus formation. J MEDICINE JUL 2019; 20 (2) : 59-62